Valuing managerial flexibility: an application of real option valuation in time of economic transition. (10th April 2015) - Cirjevskis, Andrejs; Baduns, Edmunds
The purpose of the paper is to present a real option valuation (ROV) model that will help to measure the value of managerial flexibility. The value of managerial flexibility appears to play a pivotal role nowadays, given the transition nature of Latvian economy. There are few academic works on the topic, yet none of the major companies in the Latvia have publicised ROV application. We have carried out ROV based on Scenario Planning and Strategic Alternatives. Having combined Scenario planning with Monte Carlo simulation and Risk–Neutral Probability–based ROV with alternative strategies of Company, authors provided a solution to the company's problem at hand. Thereby we have identified value maximising decisions regarding the Business Unit of the Latvian Company. The flow chart of ROV application has been created which would be a useful 'road map' for Latvian practitioners in time of economic transition.